Fast Treatment of Methamphetamine Related Anxiety and Depressive Disorders: A Novel Approach - Jamshid Ahmadi (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2016)
Background: Methamphetamine abuse and dependence is currently a considerable problem. Objective: To explain the efficacy of buprenorphine in the quick management of methamphetamine related anxiety and depressive disorders and also methamphetamine withdrawal craving. Results: 52 mg of buprenorphine is very valuable in the treatment of severe methamphetamine related anxiety and depression and also methamphetamine craving. Discussion: This study lightens that high dose of buprenorphine is quite effective in the lowering of anxiety, depression, and chest pain and methamphetamine withdrawal symptoms. Hence, our finding is a substantial addition to the literature. Conclusions: We resulted that a single high dose of buprenorphine could quickly subside methamphetamine induced anxiety, depression, psychogenic pain and withdrawal symptoms. It looks that buprenorphine may be a safe and valuable drug for the treatment of the majority of methamphetamine associated disorders.